Civilian Protection in the Gaza Conflict: A Comparative Analysis of International Humanitarian Law and Fiqh Siyar - Andini Rachmawati; Veronica Azzahra Aurel Laksono; Mohammad Sheikab Alam; Achmad Arif (UNIDA Gontor, 2026)
The Israeli–Palestinian armed conflict, particularly the hostilities in the Gaza Strip since October 2023, has caused extensive civilian casualties and severe humanitarian suffering, raising serious concerns regarding compliance with International Humanitarian Law (IHL). Although IHL provides a comprehensive framework governing the conduct of hostilities and civilian protection, persistent violations, enforcement constraints, and accountability gaps continue to undermine its protective objectives. This study examines civilian protection in the Gaza conflict through a comparative normative analysis of International Humanitarian Law and Islamic international law (Fiqh Siyar). Using a normative doctrinal legal research method with descriptive and historical approaches, this research analyzes treaty law, customary IHL, international jurisprudence, and classical and contemporary Islamic legal sources. The findings demonstrate substantive convergence between IHL and Fiqh Siyar on core humanitarian principles, including civilian immunity, limitations on methods and means of warfare, proportionality, and the primacy of humanity over military necessity. Fiqh Siyar further contributes an ethical dimension grounded in maqāṣid al-sharīʿah, particularly the protection of life (ḥifẓ al-nafs), and imposes categorical prohibitions on practices such as mutilation and collective harm. However, structural differences remain. While IHL relies on treaty consent and international enforcement mechanisms that are often politically constrained, Fiqh Siyar is rooted in religious and moral legal obligations that may enhance normative internalization. This study concludes that integrating Fiqh Siyar’s ethical insights can strengthen civilian protection frameworks in contemporary armed conflicts.